Is the Market Well Defined in Bank Merger and Acquisition Analysis? - III, William E. Jackson (The Review of Economics and Statistics, 1992)
Two hypotheses are tested in this paper. The first is whether the appropriate geographic market for certain banking services is national, instead of local. The second is whether the definition of banking "product" as all banking services is too broad. Copyright 1992 by MIT Press.